The Impact of CSR on Company Financial Performance Using Company Size as a Moderator - Azzahra, Widad Nabila; Wafdayanti, Haasya; Hersugondo, Hersugondo (LifeSciFi, 2024)
State governance with sustainable development goals cannot be separated from the SDGs. SDGs are goals, targets and indicators that have been agreed upon by countries associated with the United Nation to determine a country's political agenda and policies. This will have an impact on every activity in the country, including the economic sector. The running of a country’s economy is closely related to the banking industry which manages the flow of funds from the public, so its role in everyday life is very important. As a form of commitment to implementing sustainable economic development, from now on every bank must implement CSR to improving the quality of life and a beneficial environment. The wider CSR activities carried out by banks will indirectly have an impact on the company's customers image so that it can encourage improvements in the banking financial performance. Improving financial performance also influences the preparation of good corporate governance or is known as a moderating factor. This research aims to analyze the influence of CSR on company performance with the moderating role of firm size. Data analysis will use multiple linear regression. This research will use data obtained from the banking industry in Indonesia in the 2018-2022 time period.